Degradation and Mechanism of the Mechanics and Durability of Reinforced Concrete Slab in A Marine Environment - 吴胜兴 刘冠国 卞汉兵 吕维波 蒋建华 (China ocean engineering, 2016)
An experimental research was conducted to determine the corrosion and bearing capacity of a reinforced concrete（RC） slab at different ages in a marine environment.Results show that the development of corrosion-induced cracks on a slab in a marine environment can be divided into three stages according to crack morphology at the bottom of the slab.In the first stage,cracks appear.In the second stage,cracks develop from the edges to the middle of the slab.In the third stage,longitudinal and transverse corrosion-induced cracks coexist.The corrosion ratio of reinforcements nonlinearly increases with the age,and the relationship between the corrosion ratio of the reinforcements and the corrosion-induced crack width of the concrete is established.The flexural capacity of the corroded RC slab nonlinearly decreases with the age,and the model for the bearing capacity factor of the corroded RC slab is established.The mid-span deflection of the corroded RC slab that corresponds to the yield of the reinforcements linearly increases with the increase in corrosion ratio.Finally,the mechanisms of corrosion morphology and the degradation of the mechanical properties of an RC slab in a marine environment are discussed on the basis of the basic theories of steel corrosion in concrete and concrete structure design.